Tailgut cyst: report of three cases and review of the literature. Issue 2 (4th March 2019) - Hufkens, Ann-Sophie; Cools, Peter; Leyman, Paul
Abstract: Introduction: Tailgut cysts or retrorectal cystic hamartomas are congenital developmental lesions which are often misdiagnosed due to their rare incidence, anatomical position and variable clinical presentation. Case report: We report three clinical cases: one of a 67-year old woman with high fever and anal bulging; the second case was a 50-year old woman with diffuse abdominal pain and the third case was a 52-year old woman with high fever and no abdominal or rectal pain. The rectal examination and MRI indicated the presence of a tailgut cyst. In all the cases a complete resection through a posterior perineal route was performed. Histopathological examination confirmed the diagnosis of a tailgut cyst, with a malignant component identified in the third case. Discussion: The discussion presents a brief review of the relevant information described in the literature to highlight the cornerstones for appropriate diagnosis and treatment of a tailgut cyst. Tailgut cysts are to be considered in the differential diagnosis of retrorectal or presacral masses as malignant transformation can occur.